Toxicity of hydrogen sulfide toward sulfate-reducing bacteria Desulfovibrio piger Vib-7 - Kushkevych, Ivan; Dordević, Dani; Vítězová, Monika (Archives of microbiology, 2019)
Sulfate-reducing bacteria (SRB) belonging to the intestinal microbiota are the main producers of hydrogen sulfide and their increasing amount due to the accumulation of this compound in the bowel are involved in the initiation and maintenance of inflammatory bowel disease. The purpose of this experiment is to study the relative toxicity of hydrogen sulfide and survival of Desulfovibrio piger Vib-7 through monitoring: sulfate reduction parameters (sulfate consumption, hydrogen sulfide production, lactate consumption and acetate production) and kinetic parameters of these processes. The research is highlighting the survival of intestinal SRB, D. piger Vib-7 under the influence of different hydrogen sulfide concentrations (1-7 mM). The highest toxicity of H2S was measured in the presence of concentrations higher than 6 mM, where growing was stopped, though metabolic activities were not 100% inhibited. These findings are confirmed by cross correlation and principal component analysis that clearly supported the above mentioned results. The kinetic parameters of bacterial growth and sulfate reduction were inhibited proportionally with increasing H2S concentration. The presence of 5 mM H2S resulted in two times longer lag phase and generation time was eight times longer. Maximum rate of growth and hydrogen production was stopped under 4 mM, emphasizing the H2S toxicity concentrations to be < 4 mM, even for sulfide producing bacteria such as Desulfovibrio. The results are confirming H2S concentrations toxicity toward Desulfovibrio, especially the study novelty should be emphasized where it was found that the exact H2S limits (> 4 mM) toward this bacterial strain inhabiting humans and animals intestine.
Keywords: Microbial Sensitivity Tests; Gastrointestinal Microbiome; Humans; Sulfates; Sulfides; střeva; Hydrogen; Intestines; Lactic Acid; oxidace-redukce; sulfidy; mikrobiální testy citlivosti; Ulcerative colitis; lidé; zvířata; Toxicity; acetáty; Hydrogen sulfide; Hydrogen Sulfide; Sulfate-reducing bacteria; Desulfovibrio; vodík; Oxidation-Reduction; sulfan; střevní mikroflóra; Acetates; Animals; kyselina mléčná; sírany